Effects of chromium supplementation on blood pressure, body mass index, liver function enzymes and malondialdehyde in patients with type 2 diabetes: A systematic review and dose-response meta-analysis of randomized controlled trials - Omid Asbaghi; Fatemeh Naeini; Damoon Ashtary-Larky; Mojtaba Kaviani; Mahnaz Rezaei Kelishadi; Elham Eslampour; Sajjad Moradi; Elahe Mirzadeh; Cain C.T. Clark; Amirmansour Alavi Naeini (Elsevier, 2021)
Background: Several studies reported beneficial effects of chromium supplementation for management of type 2 diabetes mellitus (T2DM). The present study aimed to provide a systematic review and meta-analysis of randomized controlled trials (RCTs) examining the effects of chromium supplementation on blood pressure, body mass index (BMI), liver function enzymes and malondialdehyde (MDA) in patients with T2DM. Methods: PubMed, Scopus, and Embase were searched up to 15 November 2020 with no language and time restriction. RCTs that reported the effects of chromium supplementation on blood pressure, BMI, liver function enzymes and MDA in patients with T2DM were included. A random-effects model was used to compute weighted mean differences (WMDs) with 95 % confidence intervals (CIs). Between-study heterogeneity was assessed by Cochran's Q test and quantified by I2 statistic. Results: Of 3586 publications, 15 RCTs were included for the meta-analysis. Pooled effect sizes indicated that chromium significantly reduced diastolic blood pressure (DBP) (WMD): -2.36 mmHg, 95 % CI: −4.14, −0.60; P = 0.008), and MDA (WMD: −0.55 umol/l, 95 % CI: −0.96, −0.14; P = 0.008). However, chromium supplementation did not significantly affect BMI, systolic blood pressure (SBP), alanine aminotransferase (ALT), aspartate aminotransferase (AST). Meta-regression analysis did not show significant linear relationship between dose of chromium and change in BMI (p = 0.412), SBP (p = 0. 319), DBP (p = 0.102), ALT (p = 0.923), AST (p = 0.986) and MDA (p = 0.055). Conclusion: The present systematic review and meta-analysis shows that supplementation with chromium at dose of 200-1000 μg/day may reduce DBP and MDA in T2DM patients.